Developing Task-Based Writing Supplementary Material Of Descriptive Text Accompanied By Audio-Visual Media - Nuricha Dian Agustin; Widiarini Widiarini (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2021)
Abstract: In the education, writing become an important skill that must be learnt by students. It is because writing is a part of four basic skills of learning English. Eventhough there was material of descritive text for seventh grade students of MTs Al-Muslihuun, it was monotonous. Actually, students needs the material related to their life and designed in simply and attractive. This research is conducted to develop a set of task-based writing supplementary material of descriptive text accompanied by audio-visual media for grade VII students. The objects of this research were 25 students of class VII-A MTs Al-Muslihuun Tlogo in the academic year 2020/2021. This study is Research and Development model by Borg and Gall (2003) that modify by the researcher based on the need and context of the research. Here are six steps in this development: (1) conducting need analysis, (2) determine the specific material, (3) designing the product, (4) getting expert judgment, (5) revision, and (6) implementation. Questionnaires applied to obtain the data. Results of the material expert judgment shows that the product task-based writing supplementary material gets value 3.25. Results of media expert judgment shows that the video gets value 4.00. It is into the range of 3.25 ≤ x ≤ 4.00 which the product categorized “very good”. Abstrak: Dalam dunia pendidikan, menulis menjadi keterampilan penting yang harus dipelajari oleh siswa. Karena menulis merupakan bagian dari empat keterampilan dasar belajar bahasa Inggris. Meskipun terdapat materi teks deskripsi untuk siswa kelas VII MTs Al-Muslihuun, namun masih monoton. Sebenarnya siswa membutuhkan materi yang berhubungan dengan kehidupannya dan didesain secara sederhana dan menarik. Penelitian ini dilakukan untuk mengembangkan seperangkat materi pelengkap menulis berbasis tugas teks deskriptif disertai media audio visual untuk siswa kelas VII. Objek penelitian ini adalah 25 siswa kelas VII-A MTs Al-Muslihuun Tlogo tahun ajaran 2020/2021. Penelitian ini merupakan model Penelitian dan Pengembangan oleh Borg dan Gall (2003) yang dimodifikasi oleh peneliti berdasarkan kebutuhan dan konteks penelitian. Berikut enam langkah dalam pengembangan ini: (1) melakukan analisis kebutuhan, (2) menentukan materi spesifik, (3) merancang produk, (4) mendapatkan penilaian ahli, (5) revisi, dan (6) implementasi. Kuesioner diterapkan untuk mendapatkan data. Hasil penilaian ahli materi menunjukkan bahwa produk materi pelengkap menulis berbasis tugas mendapat nilai 3,25. Hasil penilaian ahli media menunjukkan bahwa video mendapat nilai 4,00. Berada pada kisaran 3,25 x 4,00 yang dikategorikan produk “sangat baik”.